(untitled) (Journal of Hama University, 2022)
The study aimed to know the reality of the use of blended learning methods in teaching from the point of view of secondary school teachers. Lattakia city, the study reached the following results: The degree of responses of the study sample members of the teachers on the axis (attitudes towards the use of blended learning methods) ranked first, with a very high degree of approval, The axis (objectives of using blended learning aids) ranked second, with a high degree of approval, and the axis (obstacles to using blended learning aids) also came with a high degree of approval and ranked third, while the axis (blended learning aids used) ranked fourth, with a medium degree of approval. And the absence of statistically significant differences between the average degrees of the responses of the study sample members to the questionnaire about the reality of blended education in teaching from the teachers’ point of view according to the variables (educational qualification, number of years of experience in teaching). And there are statistically significant differences between the average degrees of the responses of the study sample members to the questionnaire on the reality of blended learning in teaching from the teachers’ point of view according to the variable variable of training courses in the field of blended learning, “except for the obstacles to using blended learning methods” and these differences are in favor of teachers who follow one or more courses in The field of blended learning